TCT-202 Effect of Contralateral Occlusion on Index Internal Carotid Artery (ICA) Duplex Doppler Velocities: Quantitative Analysis Using Intravascular Ultrasound (IVUS) to Match Index ICA Stenosis Severity - Musialek, Piotr; Tekieli, Lukasz; Pieniazek, Piotr; Kablak-Ziembicka, Anna; Przewlocki, Tadeusz; Dzierwa, Karolina; Trystula, Mariusz; Zmudka, Krzysztof; Tracz, Wieslawa; Podolec, Piotr (Journal of the American College of Cardiology, 2012)
Nearest neighbour search algorithm was used to pair each patient with contralateral ICA occlusion with a same-gender subject with contralateral ICA patent and close-to-identical index ICA stenosis severity by IVUS criteria.